“For REASON […] is nothing but Reckoning” : the Postulates of Hobbes’s and Descartes’s Rationalism - Jean-Marc Chadelat (Revue LISA)
Thomas Hobbes and René Descartes are contemporary authors whose rationalistic approach means to emancipate science from theology. Hobbes’s Leviathan (1651) and Descartes’s Discours de la méthode (1637) expound a method which is supposed to account for the various phenomena peculiar to the physical and mental realms through a mechanistic conception including space, bodies and motion. Its object is to dispel the mystery surrounding occult forces or immaterial entities with the tenets of a rational science founded on analysis and counting, i.e. calculation. The supremacy of reason asserted at the expense of any other human faculty finds expression first of all in a tendency to reduce all things to their constitutive parts, to bring these down to the level of their corporeal modality and determine them from a quantitative angle. It is manifested secondly in an artificial subdivision of reality into as many identical elements as can be measured and apprehended. The discontinuous survey of phenomena entailed by the prevalence of quantification over qualification results in a solidification of the objective world. The exclusive rationality of the method implies a materialistic debasement of reality foregrounding a quantitative and statistic estimate to the detriment of the qualitative or essential dimension. The outcome of such an equation of intelligibility with measurement is a conspicuous simplification of the reality under study. The popularization of science brought about by the epistemic revolution of modern times thus relies on a discourse suited to its audience as well as to its object.